2014
DOI: 10.1063/1.4871011
|View full text |Cite
|
Sign up to set email alerts
|

Synchronization in a coupled architecture of microelectromechanical oscillators

Abstract: Articles you may be interested inNumerical and analytical investigation of the synchronization of dipolarly coupled vortex spin-torque nanooscillators Appl.There has been much recent interest in engineering the phenomenon of synchronization in coupled micro-/nano-scale oscillators for applications ranging from precision time and frequency references to new approaches to information processing. This paper presents descriptive modelling detail and further experimental validation of the phenomenon of mutual synch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
15
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(16 citation statements)
references
References 28 publications
0
15
1
Order By: Relevance
“…These phenomena have found practical applications in RF communication [4], signal-processing [5], novel computing and memory concepts [6,7], clock synchronization and navigation [8], as well as in phased locked loop circuits [9]. For these applications, micro-and nano-mechanical devices are known to present opportunities of integration and scalability [10][11][12][13][14][15] but more recently, optomechanical systems further emerged as new appealing candidates. Indeed they support non-linearly coupled optical and mechanical modes [16,17], and add to the mechanics the assets of optical techniques in terms of precision and long-distance communications [18][19][20][21][22][23][24][25].…”
mentioning
confidence: 99%
“…These phenomena have found practical applications in RF communication [4], signal-processing [5], novel computing and memory concepts [6,7], clock synchronization and navigation [8], as well as in phased locked loop circuits [9]. For these applications, micro-and nano-mechanical devices are known to present opportunities of integration and scalability [10][11][12][13][14][15] but more recently, optomechanical systems further emerged as new appealing candidates. Indeed they support non-linearly coupled optical and mechanical modes [16,17], and add to the mechanics the assets of optical techniques in terms of precision and long-distance communications [18][19][20][21][22][23][24][25].…”
mentioning
confidence: 99%
“…[11][12][13][14] Distinct from injection locking, mutual synchronization and mutual subharmonic synchronization occur when there is mutual, bidirectional coupling between the two oscillators. 10,[15][16][17][18][19][20] In oscillators based on micro-and nano-electromechanical systems (MEMS and NEMS) resonators, mutual synchronization is of interest because, assuming constant strain-energy density, oscillator phase noise increases as the physical volume of a resonator decreases. As a result, NEMS and MEMS-based oscillators tend to have greater phase noise than their macroscopic equivalents.…”
mentioning
confidence: 99%
“…However, it has been shown that phase noise can be reduced below the individual-resonator level by mutually synchronizing multiple resonators. 21 Synchronization in these NEMS and MEMS devices is most commonly demonstrated by coupling two different resonators either electronically 17 or mechanically via electrostatic force, 20,22 light, 23,24 or flexures. 25,26 The need to use multiple resonators in these demonstrations introduces a serious flaw in this approach, since the original goal of miniaturization is reduced size.…”
mentioning
confidence: 99%
See 2 more Smart Citations